2020
DOI: 10.1097/ajp.0000000000000841
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of Prolonged Pregabalin Administration Before and After Surgery in Patients Undergoing Arthroscopic Anterior Cruciate Ligament Repair

Abstract: Context and Objective: Reconstruction of the knee ligament causes postoperative pain and delayed rehabilitation. Objective: The primary objective of this study was to evaluate the effect of a prolonged preoperative and postoperative pregabalin use for arthroscopic anterior cruciate ligament repair. Materials and Methods: Group 1 (N=25) patients received pregabalin 75 mg/d, and group 2 (N=25) received placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In Akelma et al 17 study, mean tramadol consumption in the pregabalin group was 178.75 mg and 318.61 mg in the control group ( p < 0.05). Moreover, in Tobias et al 21 study, median tramadol consumption 24 hours after surgery was 200 mg and 400 mg in the pregabalin and control group ( p = 0.021), respectively.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In Akelma et al 17 study, mean tramadol consumption in the pregabalin group was 178.75 mg and 318.61 mg in the control group ( p < 0.05). Moreover, in Tobias et al 21 study, median tramadol consumption 24 hours after surgery was 200 mg and 400 mg in the pregabalin and control group ( p = 0.021), respectively.…”
Section: Resultsmentioning
confidence: 88%
“…Akelma et al and Tobias et al reported significantly lower postoperative opioid consumption in the pregabalin group in comparison with the control group. 17,21 However, Cho et al and Nimmaanrat et al did not find a significant difference. 19,20 Finally, Fortis-Olmedo et al 18 found significantly lower opioid consumption in the 150 mg pregabalin group in comparison with the control and 75 mg pregabalin groups.…”
Section: Resultsmentioning
confidence: 93%
“…26 A final study determined that prolonged administration of pregabalin 7 days before and after ACL reconstruction decreased the need for supplemental analgesics. 27 Thus, pregabalin may also represent a potential addition to future multimodal pain strategies in ACLRs.…”
Section: Other Measuresmentioning
confidence: 99%
“…Clinical uses of pregabalin are already well established in the treatment of neuropathic pain, post‐herpetic neuralgia, and epilepsy 6–8 . Previous studies have shown a reduction in postoperative pain and lower consumption of opioids using these drugs, but further studies are still needed to clarify their indications in this context 2,9–11 …”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Previous studies have shown a reduction in postoperative pain and lower consumption of opioids using these drugs, but further studies are still needed to clarify their indications in this context. 2,[9][10][11] This study assessed a better recovery of patients in the postoperative period by oral administration of 300 mg of pregabalin, 2 h before the surgical procedure of abdominal hysterectomy, aiming to reduce pain-as measured by the visual analogue scale (VAS) and the McGill's pain questionnaire-and as a secondary outcome, to reduce the consumption of opioids as an analgesic rescue drug. The hypothesis is that patients who received pregabalin in the preoperative period would present lower pain rates 24 h postoperatively compared to the placebo group.…”
Section: Introductionmentioning
confidence: 99%